Novel method for joint parameter estimation based on FPSD in wideband bistatic MIMO radar system - Li LI; Tian-shuang QIU (Tongxin xuebao)
A novel algorithm to jointly estimate parameters based on the fractional power spectrum density (FPSD) was proposed in wideband bistatic MIMO radar system. In many applications, it is not appropriate to approximate the wide-band signal by the narrowband model, so a novel wideband signal model was proposed to accurately estimate parameters of moving targets. Doppler stretch and time delay are estimated by searching the peak of the fractional power spectrum density (FPSD). Two subarrays are constructed based on the peak of the FPSD. Both direction of departures (DOD) and direction of arrivals (DOA) of the multiple targets are jointly estimated by employing the FPSD-MUSIC algorithm and FPSD-ESPRIT algorithm. Furthermore, the cramér-rao bound (CRB) for target parameters estimation of wideband signal model was derived. Simulation results are presented to verify the effectiveness of the proposed method.